Large inter-arm systolic blood pressure difference is associated with cognitive impairment in older adults: a cross-sectional study in rural southwest China - Wu, Qingyue; Yang, Jingyuan; Zhou, Xunqiong; Chen, Mingyan; Yang, Xing (Frontiers in Aging Neuroscience, 2025)
BackgroundStudies have shown that both inter-arm blood pressure difference (IABPD) and cognitive impairment are associated with vascular events. However, the relationship between IABPD and cognitive impairment among elderly individuals in rural China remains unclear. This study aims to investigate the association between IABPD and cognitive impairment in rural older adults in Guizhou, southwestern China.MethodsThe study data were obtained from the Cohort Study of the Health Status of Guizhou Rural Older Adults in China (SHGROC). A multi-stage cluster sampling method was employed to select 1,088 rural elderly individuals aged ≥ 60 years from Guizhou Province for questionnaire surveys, physical examinations, and biological sample collection. Cognitive function of participants was assessed using the Mini-Mental State Examination (MMSE). Bilateral blood pressure was measured simultaneously using an automated device, and the IABPD was calculated. Multivariable linear and logistic regression models were used to examine the relationship between IABPD and cognitive impairment.ResultsThe overall prevalence of cognitive impairment in the study sample was 27.85%, and it was more common among participants with an IABPD ≥ 10 mmHg (P < 0.05). Multivariable regression analysis revealed that an inter-arm systolic blood pressure difference (IASBPD) ≥ 10 mmHg was independently associated with lower MMSE scores (β = −1.113; 95% CI: −2.120, −0.106; P = 0.030) and a higher risk of cognitive impairment (OR = 1.902; 95% CI: 1.189, 3.040; P = 0.007). Additionally, a dose-response relationship was observed between IASBPD and the risk of cognitive impairment, with a linear positive correlation. Further subgroup analysis indicated that the relationship between IASBPD and cognitive impairment was modified by sex, smoking, and regular exercise (P for interaction < 0.05).ConclusionIASBPD ≥ 10 mmHg is associated with an increased risk of cognitive impairment in rural Chinese older adults. This suggested that IASBPD may provide a reference for early identification of individuals at risk of cognitive impairment.